Bovine lactoferrin suppresses the cathepsin-dependent pathway of SARS-CoV-2 entry in vitro - Kobayashi-Sakamoto, Michiyo; Maeda, Toyonobu; Yusa, Junko; Shimada, Takahisa; Tani, Hideki; Kato, Yasumasa; Hirose, Kimiharu (International dairy journal, 2024)
Severe acute respiratory coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019 (COVID-19). The frequent appearance of variants requires adjunct strategies to combat SARS-CoV-2 infections. Lactoferrin, a naturally occurring glycoprotein, exhibits promising antiviral properties. Here, we investigated the efficacy of bovine LF (bLF) against SARS-CoV-2 infection. SARS-CoV-2 pseudoviruses bearing the original Wuhan (wild-type), D614G mutant, or Omicron variant spike proteins were used to examine the effects of bLF on viral entry into host cells. We found that although bLF did not suppress entry of wild-type pseudoviruses into cells expressing both human angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine 2 (TMPRSS2), it did suppress entry of Omicron pseudoviruses into the cells. The results of this in vitro study highlight the spike protein-dependent effects of bLF on suppression of pseudovirus entry into host cells. Future clinical trials investigating the efficacy of bLF against SARS-CoV-2 infection should consider the differential impact of virus variants.